Hydatid Disease of the Femur with an Extraosseous Extent due to a Former Biopsy Complicated by a Pathological Fracture. (30th July 2012) - Ciftdemir, M.; Sezer, A.; Puyan, F. O.; Copuroglu, C.; Ozcan, M.
Abstract : Hydatid disease of the bone represents about 1–2.5% of all human hydatid disease. Spine is the most affected part of the skeleton with 50% incidence of all bone hydatidosis. Extraspinal bone hydatidosis is much rare. Diagnosis is difficult in the bone hydatid disease. Bone tumors, tumor-like lesions, and specific and nonspecific infections should be considered in the differential diagnosis. Radiological, laboratory, and clinical findings combined with strong element of suspicion are the key for diagnosis. Bone biopsies should be avoided because of the danger of anaphylaxis, sensitization, and spread. This paper describes the management of a patient with primary hydatidosis of the femur, which had been complicated by an extraosseous involvement, cortical erosion, and a pathological fracture due to a former needle biopsy.